2015
DOI: 10.1103/physrevlett.115.240401
|View full text |Cite
|
Sign up to set email alerts
|

Quasicondensation in Two-Dimensional Fermi Gases

Abstract: In this paper we follow the analysis and protocols of recent experiments, combined with simple theory, to arrive at a physical understanding of quasi-condensation in two dimensional Fermi gases. We find that quasi-condensation mirrors Berezinskiȋ-Kosterlitz-Thouless behavior in many ways, including the emergence of a strong zero momentum peak in the pair momentum distribution. Importantly, the disappearance of this quasi-condensate occurs at a reasonably well defined crossover temperature. The resulting phase … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
29
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(30 citation statements)
references
References 32 publications
1
29
0
Order By: Relevance
“…(b) Side absorption images illustrating our capability to load and resolve single (above) and multiple pancakes (below) after adiabatically increasing the lattice spacing to ∼ 12 µm. (c) In-situ absorption images of majority (above) and minority (below) clouds along the vertical direction at 755 G and polarization P = 0.6. superfluid state was explored [39,40]. The properties of the polaron were characterized in experiments studying the extreme imbalance limit [41].…”
Section: Fig 1 Experimental Setup (A)mentioning
confidence: 99%
“…(b) Side absorption images illustrating our capability to load and resolve single (above) and multiple pancakes (below) after adiabatically increasing the lattice spacing to ∼ 12 µm. (c) In-situ absorption images of majority (above) and minority (below) clouds along the vertical direction at 755 G and polarization P = 0.6. superfluid state was explored [39,40]. The properties of the polaron were characterized in experiments studying the extreme imbalance limit [41].…”
Section: Fig 1 Experimental Setup (A)mentioning
confidence: 99%
“…Hence we identify the superfluid core, a significant normal component, and a ratio of R/λ ∼ 10 2 as a possible explanation for the large universal transition exponent η trap,c 1.4. Although it is possible to include more quantitative knowledge of the quasi-2D equation of state [40][41][42][43][44] into the LCA approximation, it is clear that our qualitative findings are robust against these refinements. A full quantitative analysis of the BKT transition in the trapped gas is left for future work.…”
mentioning
confidence: 96%
“…It was important to compare these results with available data. To this end we addressed the continuum case associated with experiments on atomic Fermi gases [16,18,38] and showed reasonable agreement with experiment. More specifically we showed that T BKT as a function of attractive interaction g first exhibits a dome like feature in the fermionic regime and only when the fermionic µ becomes negative, does the BEC asymptote set in.…”
Section: Discussionmentioning
confidence: 83%